Knowledge and Awareness Regarding Osteoporosis Among A Selected Community of Miri, Sarawak - Agatha Christeeble Anak PADANG; Lay-Khim GOH; Saedah MUDA; Bit-LianYEE (Talenta Publisher, 2022)
Osteoporosis is one of the diseases concerned and has been identified as having a significant increase in the progression of aging in the world. The incidence of total hip fracture cases associated with osteoporosis is expected to increase because of the rise in the prevalence of the elderly as an effect on high life expectancy and good health services quality. Therefore, the main objective of this study is to investigate level of knowledge and awareness of osteoporosis among public in Sarawak, Malaysia. This cross-sectional study was conducted to 224 public respondents. We used questionnaire on knowledge, attitude and practices by Tripathi and colleagues. Result of this study indicated that demographic variables gender and educational level had significant association with level of knowledge among public but not for the age, races, marital status, occupational and household income variables. In conclusion, this study revealed that most respondents presented with high knowledge with high level of awareness regarding osteoporosis disease. It is recommended that to be continued the effort by local authority regarding health promotion on issues surrounding osteoporosis. Â